2012
DOI: 10.2147/opth.s28938
|View full text |Cite
|
Sign up to set email alerts
|

Cone dysfunctions in retinitis pigmentosa with retinal nerve fiber layer thickening

Abstract: PurposeTo investigate whether or not thicker retinal nerve fiber layer (RNFL) in retinitis pigmentosa (RP) patients relates to functional abnormalities of the photoreceptors.MethodsOptical coherence tomography-based RNFL thickness was measured by Stratus-3™ (Zeiss, Basel, Switzerland) optical coherence tomography and electroretinogram (ERG) recordings made using the RETI-port® system (Roland, Wiesbaden, Germany) in 27 patients with retinitis pigmentosa and in 30 healthy subjects.ResultsPhotopic ERG b-wave ampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 12 publications
1
7
1
1
Order By: Relevance
“…It has been suggested that increased RNFL thickness may be associated with cone system abnormality [30,31]. Clinical findings in our patients support this observation.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It has been suggested that increased RNFL thickness may be associated with cone system abnormality [30,31]. Clinical findings in our patients support this observation.…”
Section: Discussionsupporting
confidence: 89%
“…Increased thickness, as well as decreased thickness of the RNFL in RP, has been reported previously [30-32], however, not in molecularly confirmed RP. It has been suggested that increased RNFL thickness may be associated with cone system abnormality [30,31].…”
Section: Discussionmentioning
confidence: 49%
“…Bevacizumab was also found to induce photoreceptor damage, immune complex formation and thrombotic micorangiopathy (Julien et al, 2014). However, the few clinical studies that compared the influence of different anti‐VEGF medications on RGCL and RNFL had a relatively short follow‐up period and showed inconsistent results (Ahn et al, 2021; Kim et al, 2019; Lee, Sim, et al, 2020; Sobacı et al, 2013). Therefore, the focus of this study was to compare the impact of specific anti‐VEGF medications (ranibizumab, aflibercept and bevacizumab) on RGCL and RNFL during a 2‐year study period.…”
Section: Introductionmentioning
confidence: 99%
“…Retinitis Pigmentosa (RP) is a leading cause of blindness resulting in incurable visual impairment [ 1 ]. It is a hereditary genetic disease causing bilateral retinal degeneration.…”
Section: Introductionmentioning
confidence: 99%